Hannah's list [compact disc, unabridged] - Macomber, Debbie (Macomber, Debbie. Blossom Street novel., 2010)
On the anniversary of his beloved wife Hannah's death, Dr. Michael Everett receives a letter she had written him. In it, she reminds him of her love and makes one final request: that he marry again. Hannah specifies three women in particular that Michael should court. During the months that follow, he spends time with Winter, Leanne, and Macy, learning more about each of them and about himself.